Biodegradation and Identification of Transformation Products of Fluorene by Ascomycete Fungi - Risky Ayu, Kristanti; Hadibarata, Tony (Springer, 2015)
Fluorene belongs to the polycyclic aromatic hydrocarbons (PAHs) which are potentially carcinogenic or mutagenic. However, very few studies on biodegradation of three-ring fluorene were investigated as compared to other three-ring PAHs such as phenanthrene and anthracene. The aim of this work is to evaluate fluorene degradation by fungal strain isolated from the decayed wood in tropical rain forest, Malaysia, and examine the effectiveness of the strain for degrading fluorene in liquid culture supplemented with the nonionic surfactants. Detailed taxonomic studies identified the organisms as Pestalotiopsis species and designated as strain Pestalotiopsis sp. W15. In this study, fluorene was totally degraded by Pestalotiopsis sp. W15 after incubation for 23 days. Various analytical studies confirmed the biotransformation of fluorene by detection of two metabolites in the treated medium: indanone (R f 0.45; λ max 240 and 290 nm; t R 7.1 min and m/z 132) and salicylic acid (λ max 205, 235, 290 nm; t R 9.4 min and m/z 382). Based on these products, a probable pathway has been proposed for the degradation of fluorene by Pestalotiopsis sp. W15. None of the intermediates were identified as dead-end metabolites.